A FORENSIC LINGUISTIC ANALYSIS OF CYBERBULLYING LANGUAGE USED BY TEENAGERS ON PUBLIC SOCIAL MEDIA PLATFORMS (Contemporary Journal of Social Science Review, 2025)
This study investigates the linguistic features of cyberbullying used by teenagers on public social media platforms, with the aim of identifying patterns that hold forensic relevance. As online communication becomes a primary mode of interaction for young people, incidents of cyberbullying have increased, raising concerns about its linguistic characteristics and potential harm. Using a qualitative descriptive design supported by corpus-based analysis, the study examines 150–200 publicly accessible posts from platforms such as Reddit, YouTube, and TikTok where users self-identify as under 18. Data were collected through purposive sampling, anonymized, and categorized according to bullying type. Analysis involved lexical, pragmatic, and discourse-level examination to determine how language constructs aggression, threats, humiliation, and exclusion in online environments. AntConc software was used to identify recurring abusive terms, collocations, and escalation patterns. Findings reveal that teenage cyberbullying frequently relies on intensifiers, slang, direct insults, and repetition, with pragmatic strategies such as ridicule and mock threats playing significant roles. The study demonstrates how linguistic cues can contribute to assessing severity, intent, and harm within forensic contexts. It also highlights the need for improved online safety measures and provides insights useful to educators, law enforcement, and forensic linguists.